Effect of Cytokinins and Auxins on In-vitro Regeneration of Carnation (Dianthus caryophyllus L.) through Callusing - Maitra, S.; Ghosh, P. D.; Roychowdhury, N.; Satya, P. (International Journal of Bio-resource and Stress Management, 2023)
An attempt was made to identify suitable regeneration protocol for establishment of carnation plantlets through callusing. ‘Chabaud Super Mix’, a commercial carnation cultivar, was used for callus induction in twelve different callusing media followed by seven regeneration media in two consecutive years. The study indicated that auxin (2, 4-D & NAA) and cytokinin (kinetin & BA) are responsible for the callus production of carnation from terminal young unfurled leaf explants. Basal msmedium along with 2,4-D (10 mg l-1) and NAA (1 mg l-1) and combination of BA (3 mg l-1)+NAA (2 mg l-1) produced nodular, greenish yellow to greenish profuse callus within 8-10 days of inoculation. MS medium having BA (3 mg l-1) and NAA (2 mg l-1) initiated callus earlier. Profuse amount of nodular greenish callus was found on the MS medium having NAA (1 mg l-1) and 2,4-D (5 mg l-1). Supplementation with kinetin (2.5 mg l-1)+NAA (1 mg l-1) in MS medium resulted into earliest initiation of shoots. MS medium supplemented with kinetin (4 mg l-1)+NAA (1 mg l-1) helped in more rapid shoot development. Therefore, to get early plantlet establishment MS medium having NAA (1 mg l-1) and 2,4-D (5 mg l-1) followed by kinetin (4 mg l-1)+NAA (1 mg l-1) might be an effective choice in carnation in-vitro culture. A study on root induction of regenerated shoots of carnation revealed that MS medium supplemented with IBA (4 mg l-1)+NAA (1 mg l-1) is the most effective rooting medium among four different media compositions, imparting rooting of 98.20% shoots and hence may be utilized for better root induction of carnation explants in-vitro.